Baby In the Barn - Akinseye, Sola (Literamed Publications Nigeria Limited, 2010)
Baby in the Barn tells the story of the virgin Mary and the events that led to the birth of Jesus Christ. In this book, the tale is presented with just enough details to engage the interest of the young reader.
Keywords: Christianity; Bible Stories; Religion